Teaching grammar: issues and challenges - Norhaida Aman (UPT Bahasa Universitas Tanjungpura, 2020)
The relationship between teachers’ beliefs and their instructional practices has attracted educational researchers’ attention. The literature on teachers’ beliefs and classroom practices suggests that a sound understanding of those beliefs is extremely helpful in developing and implementing useful programs and effective in-service training. This study explores the complex relationship between the beliefs and practices of teachers from primary schools in Singapore, specifically looking at how instructional strategies are reflections of teacher beliefs on grammar instruction.Overall, the teachers who participated in this survey unanimously agree that grammar is important and has to be taught in primary school. They believe that grammar consists of rules of sentence formation, and the use of accurate tenses, and that grammar should focus on both form and meaning. Explicit discussion of grammatical rules in the classroom is thought to be extremely important in helping students acquire the English language and develop their writing skills.In terms of their classroom practices, the data suggests a more traditional approach of explicit teaching of grammar where rules and sentence structures are first taught to students and brought to their attention.